AN EVALUATION STUDY OF ENZYME-LINKED IMMUNOSORBENT ASSAY (ELISA) USING RECOMBINANT PROTEIN GRA1 FOR DETECTION OF IgG ANTIBODIES AGAINTS TOXOPLASMA GONDII INFECTIONS - Muflikhah, Nina Difla; Artama, Wayan Tunas (Indonesian Journal of Tropical and Infectious Disease, 2017)
Toxoplasmosis is an infectious disease caused by Toxoplasma gondii, an intracellular protozoan parasite that live inside the cells of the reticulo endothelial and parenchymal cells of human and animals (mammals and birds). Some cases of toxoplasmosis usually have no symptoms, but in any cases caused severe symptoms, such as hydrocephalus, microcephalus, intracranial calcification, retinal damage, brain abscess, mental retardation, lymphadenopathy, and others. Its severe symptoms usually showed a long time after first exposure, except symptoms showed by congenital transmission caused by infected mother. Early diagnosis is important to prevent the illness but methods for toxoplasmosis screening are still too expensive for developing country. Enzyme-linked immunosorbent assay (ELISA) allow the testing of a large number samples within short time frame and based on antibody or antigen detection. This study aimed to know the sensitivity and specificity of recombinat protein GRA1 as antigen using ELISA methods. We tested the sensitivity and spesificity of GRA1 protein as antigen in ELISA methods to diagnose toxoplasmosis and compared with ELISA Kit Commercial. Reliable laboratory testing is important to detect Toxoplasma gondii infection, and focused to improving the low cost and easy-to-use diagnostic instrument. Seventy sera collected and tested using both indirect ELISA, commercial ELISA kit and GRA1 protein coated as antigen. Fourty eight and fifty one samples showed positive IgG antibody result of ELISA-GRA1 and ELISA kit. Negative sample tested by ELISA-GRA1 was 22 samples and 19 sample tested by ELISA Kit. The sensitivity and specificity of GRA1-based on ELISA were 100% and 86.36%, positive prediction value (ppv) was 94.11%. These data indicate that the recombinant protein GRA1 is a highly immunogenic protein in human toxoplasmosis and become a promising marker for the screening of toxoplasmosis.